BAHAN BELAJAR MANDIRI SEBAGAI SUATU MODEL MODUL STUDI ISLAM BERWAWASAN DERADIKALISASI PEMAHAMAN AGAMA - Susanto Susanto (Perspektif Ilmu Pendidikan, 2016)
The research development model of Islamic study self-learning module with religion understanding de-radicalization is to improve students’ ability to understand the teachings of Islam without radicalism. The study began with the development of a preliminary study following the model by Borg & Gall, then the product development followed the procedures of instructional development model (MPI) resulting the final product in the form of self-study module. The validation test and product development were carried out properly according to the procedures, starting from identifying, developing and evaluating and revising. To test the effectiveness of product development, the researcher used two techniques of assessing user’s response and t- test. The results of the effectiveness test show that the module has effectively improved the students’ ability to use the methods of understanding the Islam teachings without radicalism.